Advancing Research to Eliminate Mental Illness Stigma: The Design and Evaluation of a Single-Arm Intervention Among University Students in Singapore - Subramaniam, Mythily; Shahwan, Shazana; Abdin, Edimansyah; Goh, Chong Min Janrius; Ong, Wei Jie; Tan, Gregory Tee Hng; Baig, Nawira; Samari, Ellaisha; Kwok, Kian Woon; Chong, Siow Ann (Frontiers in Psychology, 2020)
Background: Anti-stigma interventions for school and college students have been studied in several countries, but to the best of our knowledge, this has not been addressed in Singapore. The current study was designed to address this lacuna and aimed to evaluate the effectiveness of an anti-stigma intervention focusing on depression among university students in Singapore. Methods: A one-off intervention comprising education and personal contact with a person with lived experience of depression was carried out in nine consecutive sessions over six months (October 2018 to April 2019) among 390 university students. Knowledge of depression and extent of stigma towards mental illness were assessed pre- and post-intervention as well as at 3-month follow up. Results: The intervention was effective in improving depression knowledge (d = 1.09; p<0.001), and reducing social distancing (d = 0.54; p<0.001) and perceived stigma (dangerous/undesirable: d = 0.60; p<0.001 and weak not sick: d = 0.10; p<0.033) pre- to post-intervention as well as pre- intervention to 3-month follow up (p<0.005). Limitations: While 3-month follow up data indicates favourable medium-term impact on knowledge and stigma; the study lacks long-term follow-up to examine the impact of anti-stigma interventions across time. The data were collected through self-report measures; thus, social desirability bias is possible despite the assurances of confidentiality. Conclusions: Given the impact of the intervention, there is a need to consider the feasibility, challenges, and enablers of implementation of such interventions into the curriculum of university students to ensure a broader and sustained outreach and stigma reduction.